(3GdGSgGe aj GdGMUGA GdJWHjbjs - (3fGOQ TYHGf(B, (3GdShGMs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2007)
(3fXQjI GdGMJeGdGJ(B-(3GdeJZjQGJ GdYThGFjI(B-(3fXQjI GdYjfGJ(B-(3GdJbOjQ GdGMUGFj(B-(3JMdjd GdJHGjf(B-(3GNJHGQGJ cG(B2- s
Keywords: (3JMdjd GdJHGjfs; (3JbOjQ GMUGFjs; (3fXQjI GdGMJeGdGJs